An Optimality-Theoretic analysis of stress in the Bani Sulaim dialect - Al Solami, Majed (Lingua Posnaniensis, 2023)
This study presents an Optimality-Theoretic analysis of stress assignment in a Bedouin Hijazi Arabic dialect. The proposed analysis includes several constraints, among which are NONFIN, which disallows stress word-finally, FBIN, which requires words to be minimally bimoraic, IAMBIC, which requires feet to be right headed, and WSP, which stipulates that heavy syllables are stressed. Importantly, the ranking relations between these constraints solve certain issues found in previous rule-based accounts of the dialect, namely accounting for trochaic stress in disyllabic words and stress in words with final heavy syllables. Trochaic stress in previous studies was seen to result from the interaction between extrametricality and foot binarity requirements, where final syllable extrametricality is revoked only in disyllabic words in favor of satisfying foot bimoraic weight. Words with final stress, on the other hand, were not accounted for in previous studies. The current study shows that Optimality Theory adequately accounts for trochaic stress and words with a final heavy syllable.